TINDAK TUTUR HAKIM BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NO. 49 TAHUN 2009 TENTANG PERADILAN UMUM - Syahfitri Purnama (Sosio e-Kons, 2015)
Speech act is a human act that is done in nearly all activities. According to Austin, speech acts consist of the locutionary acts are acts of speaking which serves as a transfer medium to the listener, illocutionary acts are acts done in speaking which are arranged in a speech to inform something under the control of the speaker, and perlocutionary acts which is a consequences or by product of speaking. The paper is titled "Speech Acts of Judge Under the Law of the Republic of Indonesia No. 49 Year 2009 Concerning General Justice". As professional manner, speech acts of judge always maintained for the honor, dignity, ethics and good behavior in performing judicial duties and in everyday life. The Problems in this study are i) How does the use of ilocutionary acts of judge in court in terms of the Act No. 49 of 2009 on the General Justice? and ii) How is speech act used by judge from the point of politeness in court ?. This study is a qualitative study and the data retrieved by judge conversations in the court of East Jakarta. The results showed that the use of representative speech act, declarative, and the directive in court, bold on record speech acts that perform the verbal action in the most concise, straightforward, direct, as it is, without strings attached so that the proceedings run smoothly. In the positive face threatening acts used disapproval sentences and in the negative face threatening acts used the politeness as mandated in the Law of the Republic of Indonesia Number 49 Year 2009 on the General Justice. Keywords: Speech Acts, Positive and Negative Face Threats, Politeness.